Penggunaan Media Gambar dalam Pengajaran Sakubun - Merri Silvia Basri; Putri Rahayuningtyas (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Improving the professionalism of Japanese teachers is indispensable. So that the ability of teachers in delivering learning is improved. Therefore, it is necessary to hold workshops and mentoring in making learning media for Japanese teachers. Especially the learning media intended for learning sakubun. Workshop materials include, 1) Introduction to drawing media, 2) Things to be aware of using drawing media in Japanese writing teaching, 3) Benefits of using drawing media in teaching Japanese writing skills, and 4) Discussions and presentations on the use of drawing media. Methods used during workshops and mentoring are lectures, discussions, mentoring. After that, participants are guided to create drawing media and sakubun. This activity is quite successful when viewed from the enthusiasm of the participants in participating in the workshop and mentoring media making. So that it can be a motivation for teachers to be more creative in making learning media and learning about sakubun. The success of this activity was thanks to the good cooperation of community service team members with the Principal of SMA Plus Pekanbaru, Riau.